RISKS OF NONCOMPLIANCE WITH ADA FOR MOBILE DEVELOPMENT - Силивончик, Кристина (SWorldJournal, 2024)
This article analyzes the risks faced by mobile app development companies due to non-compliance with accessibility standards for people with disabilities. The study aims to examine the impact of not adhering to accessibility standards on business in terms